Hedonic Prices and the Benefits of Public Projects - Kanemoto, Yoshitsugu (Econometrica, 1988)
S. Scotchmer has shown that, even if the population is homogeneous, hedonic prices do not correctly measure long-run benefit s of a large public project. This paper examines the direction of err ors and shows that the use of cross-sectional land rent differentials leads to overestimation of the benefits. The short-run benefits with fixed lot size are also considered. Copyright 1988 by The Econometric Society.